Elderly lost & found system - Teo, Wei Jie (Nanyang Technological University, 2021)
Singapore is facing an ever-increasing aging population, which increases the burden on caregivers to care for the elderly population. Elders, especially those diagnosed with dementia, can be challenging to care for. People with dementia (PWD) require extra care and attention due to the associated disorders that can come with it. Wandering is one such behaviour that occurs frequently in PWD. Although many technological solutions exist to manage dementia wandering, they are not widely adopted in Singapore as they do not fully address the needs of the PWDs and caregivers, or that they are developed for specific countries or regions. In this project, an application system named SingTRACeX was developed, comprising a front-end mobile application with back-end support from a local server and Firebase Cloud Platform. It is designed to address the needs of PWDs and caregivers in Singapore, with the aim to minimise the negative outcomes of dementia wandering and to reduce the burden and stress on caregivers, thus improving overall well-being. The features are developed based on inputs from a multi-field study with local caregivers, and adaptations from existing solutions and related works. Features of highlight, designed to better address the needs of PWDs and caregivers, include a lost and found alert system, an indoor navigation system, and pre-lost detection. Initial test shows that the system was able to achieve desirable results in terms of correctness and robustness, with a feasibility study lined up to verify its effectiveness and feasibility for deployment in actual scenarios.